2000
DOI: 10.1002/14651858.cd000138.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Mefloquine for preventing malaria in non-immune adult travellers

Abstract: BackgroundMefloquine is commonly prescribed to prevent malaria in travellers, and has replaced other drugs because Plasmodium falciparum is commonly resistant to them. However, mefloquine may be associated with neuropsychiatric harmful effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 89 publications
2
33
0
Order By: Relevance
“…Mefloquine is effective against chloroquine resistant Plasmodium species, however there are some areas in SE Asia with known mefloquine resistance. Of note, mefloquine has been found to have serious neuropsychiatric adverse events, which limit its usefulness in certain populations (Castelli et al, 2010;Croft & Garner, 2008). Mefloquine efficacy has been shown to be greater than 90% in multiple clinical trials , the longest of which was in Peace-Corps volunteers in Africa during the early 1990's.…”
Section: Mefloquinementioning
confidence: 99%
See 2 more Smart Citations
“…Mefloquine is effective against chloroquine resistant Plasmodium species, however there are some areas in SE Asia with known mefloquine resistance. Of note, mefloquine has been found to have serious neuropsychiatric adverse events, which limit its usefulness in certain populations (Castelli et al, 2010;Croft & Garner, 2008). Mefloquine efficacy has been shown to be greater than 90% in multiple clinical trials , the longest of which was in Peace-Corps volunteers in Africa during the early 1990's.…”
Section: Mefloquinementioning
confidence: 99%
“…Mefloquine efficacy has been shown to be greater than 90% in multiple clinical trials , the longest of which was in Peace-Corps volunteers in Africa during the early 1990's. In addition, a review of mefloquine trials found that it did prevent malaria in chloroquine resistant areas (Croft & Garner, 2000). Although an effective medication, the endemic risk of malaria, current resistance patterns, the drug's side effect profile and the patient's medical and psychiatric history should be carefully considered before prescribing mefloquine (Croft & Garner, 2000).…”
Section: Mefloquinementioning
confidence: 99%
See 1 more Smart Citation
“…Mefloquine has been used for the chemoprophylaxis and treatment of malaria [1,2,3,4,5,6,7,8], schistosomes and other helminthes [9]. The use is limited by various side effects [4] including neuropsychiatric disorders [10,11,12,13,14], skin reactions [15] as well as risk of miscarriage and stillbirth [16].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] This drug is a chiral compound with two asymmetric carbon centers that result in potentially four stereoisomers. The marketed anti-malarial drug mefloquine consist of two of these isomers, the RS and SR pair (referred hereafter as (+) and (−)).…”
Section: Introductionmentioning
confidence: 99%